Effect of Bacillus cereus as a water or feed additive on the gut microbiota and immunological parameters of Nile tilapia. (5th July 2016) - Wang, Miao; Liu, Guanbin; Lu, Maixin; Ke, Xiaoli; Liu, Zhigang; Gao, Fengying; Cao, Jianmeng; Zhu, Huaping; Yi, Mengmeng; Yu, Deguang
Abstract: We evaluated the effects of Bacillus cereus, as an additive in water and feed, on the gut microbiota and immunological parameters of Nile tilapia ( Oreochromis niloticus ) fingerlings. Experiments were performed in tanks and net cages respectively. Experiment 1: Tilapia were housed in tanks for 42 days, and B .  cereus was added to the water at 1.0 × 10 4  cfu mL −1 (Treatment 1) and 1.0 ×10 5  cfu mL −1 (Treatment 2) weekly. For the control, no probiotic was added. Experiment 2: Tilapia were housed in cages for 42 days, and the feed was supplemented with B .  cereus at 1.0 × 10 7  cfu g −1 (Treatment 1) and 1.0 × 10 8  cfu g −1 (Treatment 2) weekly. For the control, no probiotic was added. Each treatment contained three replicates, with 50 male tilapias per replicate. The fish from the probiotic treatments in both tank and cage experiments had significantly higher serum lysozyme and peroxidase activities than the control. In the cage experiment, alkaline phosphatase and total superoxide dismutase activities in tilapia were significantly higher in probiotic treatments compared with the control. The results of polymerase chain reaction‐denaturing gradient gel electrophoresis showed that B. cereus supplementation in the feed and water affected the autochthonous gut bacteria community of tilapia and stimulated various potentially beneficial bacteria. Therefore, B. cereus, as a water or feed additive, could enhance the immune status and affect the gut microbiota of tilapia. Bacillus cereus was more effective as a feed supplement rather than a water additive for enhancing the immune status of tilapia.